The Curse of the Law, the Covenant, and Anthropology in Galatians 3:10-14: An Examination of Paul's Use of Deuteronomy 27:26 - Cowan, J. Andrew (Journal of Biblical literature, 2020)
For many years, the view that Gal 3:10-14 addresses the anthropological inability of sinful humans to fulfill the law was nearly universal. This interpretation, however, has recently faced serious criticisms. One of the most influential alternative readings is that Gal 3:10-14 primarily addresses the issue of Israel's corporate curse. I argue, however, that there are problems with this interpretation, despite its current popularity. A carefully nuanced version of the anthropological view provides a more satisfying reading of the text.